SPORT FACILITY MANAGEMENT IN THE SPORT HALL GELANGGANG OLAHRAGA (GOR) DELTA SIDOARJO - Rahmi, Fatimah Cahya; Pramono, Made (Jurnal Kesehatan Olahraga, 2019)
Multipurpose hall at the Gelanggang Olahraga (GOR) Delta Sidoarjo is one of facillity by Sidoarjo regency government. The Multipurpose hall is not only used for sports activities but also for activities other than sports, so it takes good facility management. In the implementation of management, there is a management process that is always used as a reference implementation of activities. The process includes planning, organizing, actuating, and controling. The aim of this research is to know the implementation management of sport facility that exist in multipurpose hall. This research method using qualitative method with research subject is manager and user of multipurpose building. (1) observation techniques, (2) documentation, and (3) indepth interviews. The result of this research showed that (1) planning is good enough, (2) organizing is  good enough, (3) actuating is good enough, and (4) controling is not good enough.   Keyword: Management, sport facility, multipurpose hall.